Analisis Pengaruh Service Quality, dan Brand Image terhadap Customer Loyalty pada BMT NU Pragaan - Moh. Helmi Hidayat; Muhibbuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract This study aims to determine the soundness of sharia business units (UUS) registered with the Islamic Financial Services Authority for 2019-2021 using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). This research method used in research is descriptive quantitative method. BMT NU Pragaan has relatively few and fixed products, marketing strategies that are still local, and competition is quite tight causing BMT NU Pragaan to only be known by some people in general. In addition, since the Corona Virus Disease 2019 (Covid-19) pandemic until now, BMT NU Pragaan has only thought about how to keep the financial institution from declining. Service quality and brand image are important to be applied by BMT NU Pragaan to increase customer loyalty, because the application of good service quality and brand image will create satisfaction for its members. Then from that sense of satisfaction, customers or members will become loyal. The purpose of this study is to first test and analyze the effect of Service Quality on Customer Loyalty at BMT NU Pragaan. Second, to test and analyze the effect of Brand Image on Customer Loyalty at BMT NU Pragaan. This research uses a quantitative approach. The type of data used is primary data obtained through questionnaires, with the sampling technique used is non-probability sampling with a sample of 75 customers. The data analysis method uses multiple linear regression methods, classical assumption tests, f-tests and t-tests. The results of research data management show that the results of the -f test obtained the value of the independent variables X1 (Service Quality) and X2 (Brand Image) simultaneously have a positive and significant effect on the dependent variable (Customer Loyality), where fcount> ftabel and a significant value of 0.000 <0.05. this shows that the Service Quality (X1), Brand Image (X2) variables simultaneously have a significant effect on Customer Loyality (Y). The t-test results obtained by the Service Quality variable value show a significant value of 0.036 <0.05. So it can be concluded that Service Quality has a positive and significant effect on Customer Loyalty. The obtained value of the Brand Image variable shows a significant value of 0.066 <0.05. So it can be concluded that Brand Image has a positive and insignificant effect on Customer Loyalty. Keywords: Service Quality, Brand Image, and Customer Loyalty